(NsPEKTROSKOPIQ PLAZMY S KWAZIMONOHROMATI^ESKIMI \LEKTRI^ESKIMI POLQMI (B/s - (NoKS(B, (NeWGENIJ aLEKSANDROWI^s ((NmOSKWA (B:s (N|NERGOATOMIZDAT(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 230-234 (131 (NNAZW(B.)s
Keywords: (NpLAZMA (B((NFIZ(B.)s; (NsPEKTROSKOPI^ESKIE ISSLEDOWANIQs; (N|LEKTRI^ESKIE SWOJSTWAs